If the equation y=mx+b is used to model a quantity y as a function of the quantity x, why is b considered to be the starting value?

Answers

Answer 1
Answer:

Answer:

This is because even when the quality of the variable x is 0, the value of b still exists and is the starting point for y.

Step-by-step explanation:

To prove this, we start with the base form of the equation and input 0 for x.

y = mx + b

y = m(0) + b

y = 0 + b

y = b



Related Questions

Please help! I dont know how to work these problems-
Why it is not reasonable to say that 4.23 is less than 4.135
Expand and evaluate the power. (1.6)^2 A. 3.6 B. 3.2 C. 2.56 D. 0.8
A blimp is 1500 meters high in the air and measures the angles of depression to two stadiums to the west of the blimp. If those measurements are 72.9° and 34.1°, how far apart are the two stadiums to the nearest meter?
How many more equal sides does an equilateral triangle have than a right isosceles triangle?

A family purchased tickets for a concert. they paid a total of $90 for 7 adult tickets and 12 child tickets. the price of a child ticket was two-thirds the price of an adult ticket. how much was the price of an adult ticket?

Answers

Price of an adult ticket is $6


Explanation:


7 adult tickets and 12 child tickets are equivalent to

(7 + 2/3 ⋅ 12) = 7 + 8 = 15 adult tickets.

So the price of an adult ticket is 90/ 15= $6


What the answer to this

Answers

First, you must know what 5^2 and 5^3 are equal to.

5^2 = 5 * 5 = 25

5^3 = 5 * 5 * 5 = 125

If x^2 is equal to 25, x = 5. If x^2 is greater than 25, x > 5. If x^2 is less than 25, then x < 5.

If x^3 is equal to 125, x = 5. If x^3 is greater than 125, x > 5. If x^3 is less than 125, then x < 5.

x^3 = 15; x < 5

x^2 = 25; x = 5

x^3 = 36; x < 5

x^2 = 49; x < 5

x^2 = 50; x > 5

x^3 = 125; x = 5

Identify the error in the student solution shown below. Find the correct answer.

Answers

Answer:

Since 0 in ln(3x) - 0 is not a logarithm, the  property of logarithms cannot be used here.

The difference shown cannot be written as a quotient of logarithms.

The step ln(x2) = ln(3x) - (0) reduces to

ln(x2) = ln(3x).

The possible solutions are 0 and 3, with 0 being extraneous.

Step-by-step explanation:

on edg

Solve the equation for y.

(y-3)^2=4y-12

Answers

(y-3)²=4y-12

First we need to start by subtract 4y-12 from both sides

y²-6y+9-(4y-12)= 4y-12-(4y-12)

y²-10y+21=0

Now we need to do the factorization of the equation

we gonna factor the left side of it

(y-3)(y-7)=0

Set factors equal to 0

y-3=0 or y-7=0

y=3 or y=7

I hope that's help :0

What are the next three numbers in this pattern 1,2,3,5,8

Answers

just add the two previous numbers together
13, 21, 34
13, 21, 34 are the next three numbers

What is y+6x=11; 3x+2y=-2?

Answers

The answer is y=5 and x=83.


ヽ(◉ ͜ʖ◉)ノ







y+6x=11; 3x+2y=-26x+y+6x=11+6x(Add -6x to both sides)
y=6x+11
Substitute6x+11foryin3x+2y=−2
3x+2y=−2
3x+2(6x+11)=2
9x+22=−2(Simplify both sides of the equation)
9x+22+−22=−2+−22(Add -22 to both sides)
9x=24
9x/−9=−24/−9(Divide both sides by -9)
x=8/3